A Serological Survey of Enteric Parvovirus Infections in Finnish Fur-Bearing Animals - Veijalainen, Pirjo (Acta Vet Scand, 1986)
Parvovirus infections in Finnish fur animals, i.e. ferrets, raccoon dogs, blue foxes and mink, were studied. The ferret was found to be the only insusceptible animal. Parvo enteritis of raccoon dogs, reported since 1980, has spread from East Finland to other parts of the country. A new candidate for the Parvovirus family was found to infect blue foxes. According to serologic investigations, the virus resembled feline panleukopenia virus more than canine parvovirus. Clinical signs during the infection have been mild. Annual vaccination has not eradicated mink enteritis virus on farms, but the disease has taken a subclinical form.